2020
DOI: 10.1017/pab.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Late Ordovician ecosystem dynamics before and after the Richmondian invasion reveal consequences of invasive species in benthic marine paleocommunities

Abstract: A thorough understanding of how communities respond to extreme changes, such as biotic invasions, is essential to manage ecosystems today. Here we constructed fossil food webs to identify changes in Late Ordovician (Katian) shallow-marine paleocommunity structure and functioning before and after the Richmondian invasion, a well-documented ancient invasion. Food webs were compared using descriptive metrics and cascading extinction on graphs models. Richness at intermediate trophic levels was underrepresented wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Past studies of the overall Richmondian Invasion have found that interspecific competition was an important factor in Cincinnatian brachiopod communities (Tyler and Leighton 2011). The fauna of the Cincinnati Sea experienced elevated levels of niche partitioning (Patzkowsky and Holland 2007), niche evolution (Malizia and Stigall 2011; Brame and Stigall 2014), and food web restructuring (Kempf et al 2020) following the overall Richmondian Invasion. This study further demonstrates that these competitive interactions developed as rapid responses to the influx of invaders during a single invasion pulse, not as a gradual, cumulative process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies of the overall Richmondian Invasion have found that interspecific competition was an important factor in Cincinnatian brachiopod communities (Tyler and Leighton 2011). The fauna of the Cincinnati Sea experienced elevated levels of niche partitioning (Patzkowsky and Holland 2007), niche evolution (Malizia and Stigall 2011; Brame and Stigall 2014), and food web restructuring (Kempf et al 2020) following the overall Richmondian Invasion. This study further demonstrates that these competitive interactions developed as rapid responses to the influx of invaders during a single invasion pulse, not as a gradual, cumulative process.…”
Section: Discussionmentioning
confidence: 99%
“…Cincinnatian strata record a regional biotic interchange known as the Richmondian Invasion which occurred through a series of pulses and introduced more than 60 novel genera into the Cincinnati Sea (Holland 1997; Stigall 2010; Lam and Stigall 2015). Numerous studies of this biotic interchange, most of which examined the entire invasion interval, have been conducted, and general ecological and evolutionary patterns have been identified (e.g., Holland and Patzkowsky 2007; Patzkowsky and Holland 2007; Malizia and Stigall 2011; Tyler and Leighton 2011; Brame and Stigall 2014; Kempf et al 2020). However, the individual pulses of the invasion have received less study (but see Schwalbach 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Primary productivity was modelled as a function of the density of herbivorous interactions [13], scaling productivity as ten times that of herbivore richness in accordance with general assimilation efficiency between trophic levels (e.g. [14,15]). Differences between pre-and post-extinction stability and resistance would also suggest that trophic restructuring occurred, altering palaeocommunity stability.…”
Section: (E) Modelling Of Palaeocommunity Dynamicsmentioning
confidence: 99%
“…Successive analyses of trophic structure over deep time can be employed to assess important ecological questions. Recently developed food web models are a powerful tool for exploring and quantifying community dynamics, simulating how the structures of modern [9][10][11][12] and ancient [7,[13][14][15][16][17] communities influence their responses to perturbations. Therefore, we provide results from cascading extinction on graphs (CEG) modelling [13] of terrestrial ecosystems to quantify community resistance during the G-L, P-Tr and T-J transitions.…”
Section: Introductionmentioning
confidence: 99%
“…While coarse, this approach reduces issues associated with finer delineations of traits, particularly when considering extinct organisms. As in modern assemblages (e.g., (Eklöf et al 2013)), functional trait data have been used to consider ancient food web structure (e.g., (Kempf et al 2020)), on the basis that functional ecology is connected to trophic interactions and food web structure (e.g., (Eklöf et al 2013; Cirtwill and Eklöf 2018)).…”
Section: Introductionmentioning
confidence: 99%